Giant cells: multiple cells unite to survive - Hazra, Shreyasee; Kalyan Dinda, Suman; Kumar Mondal, Naba; Hossain, Sk Rajjack; Datta, Pratyay; Yasmin Mondal, Afsana; Malakar, Pushkar; Manna, Dipak (Frontiers in Cellular and Infection Microbiology, 2023)
Multinucleated Giant Cells (MGCs) are specialized cells that develop from the fusion of multiple cells, and their presence is commonly observed in human cells during various infections. However, MGC formation is not restricted to infections alone but can also occur through different mechanisms, such as endoreplication and abortive cell cycle. These processes lead to the formation of polyploid cells, eventually resulting in the formation of MGCs. In Entamoeba, a protozoan parasite that causes amoebic dysentery and liver abscesses in humans, the formation of MGCs is a unique phenomenon and not been reported in any other protozoa. This organism is exposed to various hostile environmental conditions, including changes in temperature, pH, and nutrient availability, which can lead to stress and damage to its cells. The formation of MGCs in Entamoeba is thought to be a survival strategy to cope with these adverse conditions. This organism forms MGCs through cell aggregation and fusion in response to osmotic and heat stress. The MGCs in Entamoeba are thought to have increased resistance to various stresses and can survive longer than normal cells under adverse conditions. This increased survival could be due to the presence of multiple nuclei, which could provide redundancy in case of DNA damage or mutations. Additionally, MGCs may play a role in the virulence of Entamoeba as they are found in the inflammatory foci of amoebic liver abscesses and other infections caused by Entamoeba. The presence of MGCs in these infections suggests that they may contribute to the pathogenesis of the disease. Overall, this article offers valuable insights into the intriguing phenomenon of MGC formation in Entamoeba. By unraveling the mechanisms behind this process and examining its implications, researchers can gain a deeper understanding of the complex biology of Entamoeba and potentially identify new targets for therapeutic interventions. The study of MGCs in Entamoeba serves as a gateway to exploring the broader field of cell fusion in various organisms, providing a foundation for future investigations into related cellular processes and their significance in health and disease.